Correction: Health and economic benefits of achieving hepatitis C virus elimination in Pakistan: A modelling study and economic analysis - Lim, Aaron G.; Scott, Nick; Walker, Josephine G.; Hamid, Saeed; Hellard, Margaret; Vickerman, Peter (PLoS medicine, 2024)
[This corrects the article DOI: 10.1371/journal.pmed.1003818.].